2023
DOI: 10.3390/ijms24021747
|View full text |Cite
|
Sign up to set email alerts
|

IL-17A Enhances Retinal Neovascularization

Abstract: Retinal neovascularization occurs in proliferative diabetic retinopathy, neovascular glaucoma, and age-related macular degeneration. This type of retinal pathology normally occurs in the later stages of these ocular diseases and is a prevalent cause of vision loss. Previously, we determined that Interleukin (IL)-17A plays a pivotal role in the onset and progression of non-proliferative diabetic retinopathy in diabetic mice. Unfortunately, none of our diabetic murine models progress to proliferative diabetic re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 23 publications
(35 reference statements)
0
2
0
Order By: Relevance
“…Recent studies have found that diabetes-mediated IL-17A enhances VEGF production in the retina, Muller glial cells, and retinal endothelial cells, and that IL-17A induces retinal endothelial cell proliferation and can enhance VEGF-dependent vascular neovascularization. Finally, a model of oxygen-induced retinopathy showed that IL-17A promotes retinal neovascularization ( 23 ). The current literature is more scattered in showing IL-17A as a possible cause of DR pathogenesis, but none of the more scientific studies have established the inevitability of their relationship.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have found that diabetes-mediated IL-17A enhances VEGF production in the retina, Muller glial cells, and retinal endothelial cells, and that IL-17A induces retinal endothelial cell proliferation and can enhance VEGF-dependent vascular neovascularization. Finally, a model of oxygen-induced retinopathy showed that IL-17A promotes retinal neovascularization ( 23 ). The current literature is more scattered in showing IL-17A as a possible cause of DR pathogenesis, but none of the more scientific studies have established the inevitability of their relationship.…”
Section: Discussionmentioning
confidence: 99%
“…However, IL-17 also contributes to an inflammatory environment that can adversely affect endothelial cell function and angiogenesis. For instance, IL-17 has been shown to increase the production of pro-inflammatory cytokines and chemokines, which can lead to endothelial dysfunction and impaired angiogenic response [ 83 , 84 ].…”
Section: Targeting Il-17 Pathways For Enhanced Healing In Chronic Wou...mentioning
confidence: 99%
“…In the peripheral blood mononuclear cells of patients with proliferative diabetic retinopathy (PDR), IL-35 lowers IL-17 levels and inhibits Th17 cell differentiation, offering protection against PDR ( 167 ). The proinflammatory cytokine IL-17 is elevated in the plasma and vitreous of diabetic patients, and the worsening of DR is linked to increased retinal IL-17A expression through Act1 signaling, which leads to Müller cell dysfunction ( 168 , 169 ), and promotes retinal neovascularization ( 170 ). In PDR, vitreous IL-17A levels are associated with IL-10, IL-22, and TNFα levels in the aqueous humor and vitreous ( 171 ).…”
Section: Retinal Inflammation In Diabetic Retinopathymentioning
confidence: 99%